Factores desde la gestión de la política y la población que influyen positiva o negativamente para que sigan consumiendo los productos contaminados del rio Huepetuhe, región Madre de Dios en el periodo 2019 al 2021 - León Rosales, Julio Eduardo (2024)
This work aims to identify the factors from the management of the policy and the population that positively or negatively influence so that the population of Huepetuhe continues to consume the contaminated products from the Huepetuhe Riverlocated in theMadredeDios regiontopropase recommendations thatmakeit possibleto promete the right to health of the population. Themethodology usedin this research is basedonconcordance forthe achievement of the objectives of the research,adopting the qualitativestrategy and the form of research is the case study; in view of the fact that it is about understanding the customs related to the food intake of the inhabitants of the district of Huepetuhe; and the actions of public managers related to the management public of these territories. The methodological strategy applied for the collection of information is mixed and includes the questionnaire as the main instrument for collecting information from households; focus group applied to a group of parents to discuss and capture the perception related to the research variables; the semi-structured interview based on the conversation mainly withpublic managers and the documentary review. The main findings show that the population maintains its eating habits based on a subsistence economy taking advantage ofthe naturalresources found intheforest,the river and developing activities of hunting, fishing to meet their food needs and as a source of income generation, through the commercialization of these products with familiesandinmarkets.Thefamilyeconomy ofHuepetuheisbased onsubsistencefrom the collection and extraction of natural resources for their use, and the local population observes that miningactivity is a source potential economic income that would alleviate their familyeconomy. Research shows us that the development of prevention and health promotion for the population is absent at the preventive levels; and in cases of needing the healing of Sorne ailment, the rural population resorts to wise people, showing their attitude and willingnesstostay ingood condition, a fact that is constituted forindigenouscommunities or native peoples in a demand to the State forthe fulfillment of the right to health. The findings show that the management of regional health policy and territorial articulation show a weak intervention for the realization of preventive communication actions for the health of the population, even when they are related to the Minamata Convention, which is a commitment to compliance at the country level. Finally, he considered that the management of regional health policies needs to be decentralized and implement prevention and health promotion services in budget programs and projects for territorial articulation; Taking into consideration the right to health of families, their cultural rights in the sustainable use of natural resources and integrity so that these populations carry a dignified life.